The vergence of technology and innovation in modern complex space - Kharchenko, Julia; Kharchenko, Sergej; Klochek, Lilia; Kluenko, Eduard; Rusul, Oleg (Journal of the University of Zulia, 2022)
The purpose of the study is to conceptualize the phenomenon of vergence of technologies and innovations in the context of building a society as a complex system by modernizing the innovation environment. To achieve the goal, general scientific and special-scientific methods of cognition were used, in particular, dialectical, formal-logical, analysis and synthesis, system-structural. The key methodological principles, spatial-topological and ontological, were presented. It is confirmed that the concept of "vergence" is the state of systems at the point of intersection of divergent and convergent processes, as well as their balancing. Vergence as a method of creative thinking was used in this study primarily to solve problems and tasks related to the synchronism of various contradictory processes (reconciles the processes of "scattering", "acceleration" and "gathering", "braking"). The value of this approach was in finding multiple solutions to ambiguous problems. The results of the study confirmed that the vergent interaction of technologies and innovations, the merging of funds and resources that contribute to the modernization of the innovation space, their analysis and synchronism, excluded the position of rest in the social system and, on the contrary, gave rise to a situation of accelerated but controlled dynamism.